Implementasi Program Keselamatan dan Kesehatan Kerja Pada Pegawai PT PLN UP3 Semarang - Dwi Wijayanti; Maria Augustine Graciafernandy; Moeljono Moeljono (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to analyze and describe the Occupational Safety and Health (K3) program implemented by PDKB PT. PLN (Persero) UP3 Semarang. The program is an effort to create a healthy and safe work environment, so as to reduce the number of work accidents or negligence which result in demotivation and work productivity deficiencies.This research is descriptive qualitative research. By taking respondents from several sources who are considered worthy of being research sources. The results of the research are that the program for implementing work safety and occupational health (K3) is carried out optimally so as to minimize the occurrence of occupational hazard risks including the availability of health clinics, medical examinations, K3 training and the use of Personal Protective Equipment. This OSH program still addresses some of the obstacles encountered which may affect the implementation of Occupational Safety and Health, namely they are still being discovered, so there is a need for a more intense understanding in applying the training program.